1971
DOI: 10.1042/bj1220249
|View full text |Cite
|
Sign up to set email alerts
|

The pathway of pepsin-catalysed transpeptidation. Evidence for the reactive species being the anion of the acceptor molecule

Abstract: 1. The inhibition of pepsin-catalysed hydrolysis of N-acetyl-l-phenylalanyl-l-phenylalanylglycine by the acyl product and product analogues was studied at pH4.3. 2. The acyl product, N-acetyl-l-phenylalanine, gives rise to linear competitive inhibition at pH4.3, whereas at pH2.1 it shows linear non-competitive behaviour. 3. The extent of transpeptidation to N-acetyl-l-[(3)H]phenylalanine during the pepsin-catalysed hydrolysis of N-acetyl-l-phenylalanyl-l-phenylalanyl-glycine is significant at pH4.7, but is und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1971
1971
1994
1994

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The experiments reported in the present paper are an extension of observations on pepsin-catalysed acyl transpeptidations (Takahashi et al, 1974;Takahashi & Hofmann, 1975) and on amino transpeptidations studied by a number of workers (Neumann et al, 1959;Fruton et al, 1961;Kozlov et al, 1966;Mal'tsev et al, 1966;Denburg et al, 1968;Silver & Stoddard, 1972;Kitson & Knowles, 1971b;Jackson etal., 1969;Terada etal., 1971). In particular, an attempt was made to obtain quantitative data for the transpeptidation and hydrolysis reactions.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The experiments reported in the present paper are an extension of observations on pepsin-catalysed acyl transpeptidations (Takahashi et al, 1974;Takahashi & Hofmann, 1975) and on amino transpeptidations studied by a number of workers (Neumann et al, 1959;Fruton et al, 1961;Kozlov et al, 1966;Mal'tsev et al, 1966;Denburg et al, 1968;Silver & Stoddard, 1972;Kitson & Knowles, 1971b;Jackson etal., 1969;Terada etal., 1971). In particular, an attempt was made to obtain quantitative data for the transpeptidation and hydrolysis reactions.…”
Section: Discussionsupporting
confidence: 61%
“…The high yields observed in our studies contrast with the low yields of transpeptidation observed previously. For example, Kitson & Knowles (1971b) found with Ac-Phe-Phe-Gly as substrate and acetyl[3H]phenylalanine as acceptor 7.5 % transpeptidation and 85 % hydrolysis. Although the specificity studies with small substrates (Fruton, 1970) show a preference for aromatic residues in the primary binding sites S, and S',, the highest yields of transpeptidation are obtained when a leucyl residue is transferred, whereas both the rates of reaction and the yields are lower when phenylalanine and tyrosine residues are transferred.…”
Section: Discussionmentioning
confidence: 99%
“…If the substrate for the formation of E *XY from EY is the anion X-, then microscopic reversibility demands that the X moiety of the substrate that is released first be released as its anion. This important point is discussed more fully in the following paper (Kitson & Knowles, 1971), but it can be said here that this superficially surprising phenomenon is required by the mechanism for pepsin proposed by Knowles et al (1970). The postulate does not affect the explanation given above for the inhibition by the other compounds studied, and indeed neatly explains the failure to detect product diversion by any neutral species such as N-methanesulphonyl-Lphenylalanine methyl thiol ester, N-acetyl-Lphenylalanine ethyl ester and N-acetyl-L-phenylalanine amide (Kitson & Knowles, 1971).…”
Section: K+2k+3[e]mentioning
confidence: 67%
“…However, pathways (e) and (f ) predict that these compounds would act as amino group acceptors with the concomitant release of ethanol and ammonia respectively. That this does not occur has been demonstrated both for the ester ) and for the amide (Kitson & Knowles, 1971). Thus it appears that pathway (d) applies, and that these two compounds inhibit the forward reaction both by competing with substrate for the active site of the free enzyme and also by combining with the intermediate amino-enzyme in a non-productive mode, presumably blocking that part of the active site previously vacated by the first product X.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation